Faktor Yang Mempengaruhi Return On Invested Capital: Studi pada Perusahaan Sektor Lembaga Keuangan Non Bank yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Munawar, Aang; Zarazetari, Refazira; Srihandoko, Wimpi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The development of the business world is increasingly rapid accompanied by intense competition, making companies must be able to survive, one of which is by improving financial performance. Non-bank financial institution sector companies are one of the pillars of economic development. However, in the last five years, mining sector companies have experienced fluctuations in company profits due to the impact of the covid 19 pandemic, causing a decline in the company's financial performance. This research was conducted to examine the effect of intellectual capital, growth ratio, liquidity (cash ratio), efficiency (net profit margin), effectiveness (total asset turnover), and leverage (debt to asset ratio) on companies in the non-bank financial institution sector on the IDX. There are 58 population of mining sector companies listed on the IDX. The sample of this research is 35 companies' financial statements obtained by using purposive sampling method. The analytical method used is panel data regression analysis with eviews 12 tools. The results showed that intellectual capital, net profit margin, total asset turnover had a positive effect on return on invested capital (ROIC), growth ratio had a negative effect on return on invested capital (ROIC), while cash ratio and debt to asset ratio no effect on return on invested capital (ROIC). simultaneously intellectual capital, growth ratio, cash ratio, net profit margin, total asset turnover, and debt to asset ratio jointly influence return on invested capital (ROIC). Keyword : Intellectual Capital, Growth Ratio, Cash Ratio, Net Profit Margin, Total Asset Turnover, and Debt to Asset Rasio